Die behoeftes en probleme van die vrou met karsinoom van die mammae wat verband hou met psigososiale, ekonomiese, seksuele en godsdienstige aspekte - N.C. van Wyk (AOSIS, 1992)
The psychosocial, economic, sexual and religious related needs and problems of women with carcinoma of the breast are explored. White women with carcinoma of the breast experience particular needs and problems related to psychosocial, economic, sexual and religious matters. These needs and problems are also influenced by a number of aetiological factors. Apart from the tension caused by a diagnosis of carcinoma, and particularly one of carcinoma of the breast, the treatment which these women receive contributes to their needs and problems. The research clearly showed that the majority of women did not experience serious problems in coping with their illness • there was a universally low average intensity of needs and problems. They did, however, require help and support in coping with and accepting the consequences of the carcinoma and the attendant treatment.